The role of digital technology-based Islamic education in strengthening social cohesion: a case study of Aceh’s madrasahs after the Helsinki accord - Irwansyah, Irwansyah (Jurnal Mantik, 2025)
This study investigated the impact of integrating digital technology into Syariah-based Islamic education on student learning outcomes and social cohesion in ten madrasahs across Banda Aceh, a region that the 2005 Helsinki Peace Accord has shaped following decades of conflict. Employing a sequential explanatory mixed-methods design, the research combined survey data from 500 students with qualitative interviews and focus group discussions involving educators, students, and religious leaders. Digital tools—such as Islamic e-learning platforms, interactive da’wah applications, and multimedia Qur’an modules—were examined for their influence on academic engagement, critical thinking, and intergroup harmony. Quantitative analysis revealed significant positive relationships between technology-enhanced instruction and student motivation, critical reflection, and civic responsibility. Structural Equation Modeling (SEM) showed that student engagement partially mediated the relationship between digital pedagogy and social cohesion (total effect ? = 0.68, p < .001). Thematic analysis indicated that technology reinforced Islamic learning, promoted inclusivity, and gained wider acceptance when framed within Syariah values and supported by local ulama. The findings suggest that, when thoughtfully implemented, digital Islamic education can act as a peacebuilding mechanism. Recommendations include teacher training, institutional investment, involvement of ulama, and long-term evaluation for sustainability and replication